Social innovation: structural strengths and restraints, an observation from social systems theory - Verdejo, Diego (MAD, 2019)
This research aimed to know how social innovation initiatives can be stabilized in the terms proposed by the evolution theory developed by Niklas Luhmann. To achieve this goal, interviews were conducted with people with experience in social innovation and performing diverse roles in spheres of society. The results show that coordination of social actors should be encouraged based on shared construction, both of the observed problems and their solutions, and if actors operate primarily with cognitive expectations, social innovation initiatives would be more likely to be stabilized.